2004
DOI: 10.1103/physrevstab.7.120101
|View full text |Cite
|
Sign up to set email alerts
|

Heavy ion storage ring without linear dispersion

Abstract: A possible method to realize a dispersion-free storage ring is described. The simultaneous use of a magnetic field B and an electric field E in bending regions, where the two fields are set perpendicular to each other, enables us to control the effect of momentum dispersion. When the relation 1 1= 2 0 E ÿv 0 B is satisfied for a beam with the velocity v 0 , the linear dispersion can be completely eliminated all around the ring. It is shown that the acceleration and deceleration induced by the electrostatic def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…It has been concluded that a beam phase transition to 1D string or 2D zigzag is feasible by the conventional Doppler cooling technique, provided that a sufficiently powerful laser is employed together with the SBRC technique. The production of a 3D crystalline beam further requires the so-called tapered cooling [12,30] or a combination of dispersionfree bending elements [31] and a coupling cavity [10,32], in order to avoid shear heating.…”
Section: Resultsmentioning
confidence: 99%
“…It has been concluded that a beam phase transition to 1D string or 2D zigzag is feasible by the conventional Doppler cooling technique, provided that a sufficiently powerful laser is employed together with the SBRC technique. The production of a 3D crystalline beam further requires the so-called tapered cooling [12,30] or a combination of dispersionfree bending elements [31] and a coupling cavity [10,32], in order to avoid shear heating.…”
Section: Resultsmentioning
confidence: 99%
“…This condition is completely the same as the dispersion-free condition shown in Ref. [14]. When the dispersion-free condition qV 0 = 2 0 2 0 E 0 1 is imposed, the equations of motion become…”
Section: Single Particle Dynamics In Dispersion Suppressorsmentioning
confidence: 81%
“…We reported the beam dynamics in a dispersion-free storage ring S-LSR constructed with the cylindrical dispersion suppressor of the field index 1 [14]. The result is that S-LSR cannot operate satisfying the maintenance condition for crystalline beam due to the strong radial focusing of the cylindrical dispersion suppressor.…”
Section: A Deflectors For a Dispersion-free Storage Ringmentioning
confidence: 99%
See 2 more Smart Citations